Jerusalem [videorecording (DVD)] - Cumberbatch, Benedict, 1976- (Arcane Pictures, 2015)
National Geographic is proud to present Jerusalem, a large format 3D/2D film made for IMAX, giant screen, and digital cinemas that immerses audiences in this ancient city and the Holy Land as never before. Using the world's most advanced film technology, Jerusalem plunges audiences into the ancient alleys and vibrant neighborhoods of Jerusalem's Old City and soars with the first-ever large format aerial views of iconic sites cherished by billions of people: the Western Wall, the Dome of the Rock, the Church of the Holy Sepulchre, the Jordan River, the Sea of Galilee, and the mountain fortress of Masada. Destroyed and rebuilt repeatedly over 5,000 years, Jerusalem's enduring appeal remains a mystery. How did it become so important to so many people? What made it the most fought over piece of land in history? Why does it still matter? The filmmakers of Jerusalem seek to increase public understanding of this incredible city, as well as foster dialogue and respect between Jews, Christians, and Muslims. - Publisher.